Walker, Texas Ranger. The complete second season - Norris, Chuck; Gilyard, Clarence, Jr., 1955-2022.; Willingham, Noble, 1931-2004.; Wilson, Sheree J.; Columbia Broadcasting System, Inc.; Paramount Home Entertainment (Firm); CBS DVD (Firm) (Hollywood, CA : Paramount Home Entertainment : CBS DVD, 2007)
A veteran lawman with a two-fisted sense of justice tackles the most hardened criminals.
Disc 1: Badge of honor ; Branded ; Silk dreams ; Mustangs -- Disc 2: 'Til death do us part ; Rainbow warrior ; The road to Black Bayou -- Disc 3: Line of fire ; Payback ; Tiger's eye ; The big bingo bamboozle -- Disc 4: Money train ; Mean streets ; Cowboy -- Disc 5: War zone. Pts. 1 & 2 ; Trust no one ; Blue movies -- Disc 6: One scared ground ; Case closed -- Disc 7: Flashback ; Standoff. Pts. 1 & 2.
Title from container.
Originally broadcast as a television series in 1994-1995.
Chuck Norris, Clarence Gilyard, Jr., Noble Willingham, Sherre J. Wilson.
Rating: Not rated.
DVD, region 1, full screen presentation: Dolby Digital.
English (stereo. surround) Spanish (mono.) or Portuguese (mono.) dialogue, Spanish or Portuguese subtitles; closed-captioned.
Keywords: Texas Rangers -- Drama; Law enforcement -- Texas -- Drama; Criminal investigation -- Texas -- Drama; Action and adventure television programs; Television cop shows; Video recordings for the hearing impaired